(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2013)
In a study conducted in three southern districts (Bhola, Borguna and Patuakhali) of Bangladesh, a total of 69 tree species was recorded from the homegardens, of which 32 were fruit tree and 37 were timber tree species. Among the fruit tree species, coconut, betel nut, mango, jackfruit, guava, velvety apple were found in more than 80% households. The stocking of fruit trees per homestead was found highest for betel nut (265) followed by velvety apple (212), mango (38) coconut (25), jackfruit (20) and guava (9). Among the timber tree species, rain tree, mehogoni, raj koroi were most prevalent and found in more than 65% homesteads. The stocking of timber trees/ homestead was found highest for mehogoni (79) and then for rain tree (57), raj koroi (29) and katbadam (6). J. Asiat. Soc. Bangladesh, Sci. 39(1): 83-94, June 2013 DOI: http://dx.doi.org/10.3329/jasbs.v39i1.16037